KEWAJIBAN MENGAJAR DALAM AL-QUR'AN - Devany Ari Susanti (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2024)
A Muslim is obliged to seek knowledge. The position of knowledge is the main thing in the Islamic religion, regardless of age, gender or social status, everyone is required to study until the end of life. The process of seeking knowledge certainly cannot be separated from an educator, and the best educator is the Prophet Muhammad Sallallaahu 'Alaihi Wa Sallam, in whose treatise there is an order to practice knowledge or teach. We can see this in the Al-Qur'an and supporting evidence, namely As-Sunnah. The type of research used in this research is a descriptive qualitative approach method and a library research approach. The results of this research are that there is an obligation to teach, practice the knowledge possessed in the Al-Qur'an and As-Sunnah, which is applied with all efforts to achieve the best results, with sincerity without expecting anything in return except only from Allah Subhanahu Wa Ta'ala.